ECG classification and the "heart age" prediction using machine learning - Shen, Y (2020)
Cardiovascular disease (CVD) is the leading cause of morbidity and mortality worldwide. Electrocardiogram (ECG) is an important clinical measurement of cardiac activity. The major challenge in incorporating ECG time-series into CVD risk metrics is extracting features and classifying the ECG time-series into appropriate ECG abnormality groups. Therefore we set out to use machine learning to address this challenge.